Implementation of the Profile Matching Method in Developing a Decision Support System for Direct Cash Assistance (BLT) in Pangestu Village - Made Putra Astama (Institute of Information Technology and Social Science (IITSS), 2024)
Pangestu Village is located in a tidal swamp area approximately 0.5 meters above sea level, with a population of around 2,000 residents. The village is bordered by Delta Upang Village to the north, Tirta Kencana and Pendowoharjo to the north, Purwosari (formerly SP3) and Muara Baru to the south, Tanjung Baru Village (Banyuasin II District) to the west, and Upang Makmur (Sahang River) to the east, adjacent to Air Salek District. Due to the high number of underprivileged households, Pangestu Village qualifies for Direct Cash Assistance (BLT), a government program designed to support low-income citizens. However, the village currently lacks an integrated information system to manage BLT data efficiently and securely. This study develops a mobile web-based Decision Support System (DSS) using the Profile Matching method to assist local authorities in identifying eligible recipients based on predefined criteria. The system allows administrators to store, process, and evaluate data securely while enabling residents to verify recipient lists transparently. The criteria used include age, number of dependents, occupation, income level, employment status, and housing condition. The application was built using PHP and MySQL technologies and successfully implemented to improve the efficiency and accuracy of the BLT recipient selection process.